Old Age and Their Conceptions in the Political Field: A Psychosocial Analysis of LGBTQI+ Old Age from the social representations of municipal parliamentarians - da Silva Alves, Mateus Egilson; Fernandes de Araújo, Ludgleydson; da Silva Sousa, Evair Mendes; de Lima Bezerra, Igor Eduardo; Lima Silva, Maria Fernanda; Aguiar Trevia Salgado, Ana Gabriela (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
This article aimed to apprehend the social representations of LGBTQI+ old age among municipal legislative managers. Participated 10 parliamentarians, with an average age of 47.6 years (Dp 8.48). Sociodemographic questionnaires and semi-structured interviews were used, later transcribed and analyzed using Bardin's content analysis method. Two empirical categories resulted from the analyzes: (1) Aging and Old Age: paradigms surrounding public practices (2) (In) equality in the political arenas about LGBTQI+ Old Age. It’s argued that the representations are anchored in the overlap between aging and old age as similar processes, justifying how they aim at public attitudes and underline elderly LGBTQI+ people involved in (in) equality. Expected to contribute to the expansion of knowledge about the psychosocial aspects of old age LGBTQI+, as well as giving rise to a debate about the need for greater attention to the plurality of gender, sexuality, and old age in the political field.